Electron momentum-transfer collision frequency measurements in small plasma objects via coherent microwave scattering. (1st November 2022) - Patel, Adam R; Wang, Xingxing; Braun, Erik L; Ranjan, Apoorv; Slipchenko, Mikhail N; Macheret, Sergey; Shneider, Mikhail N; Shashurin, Alexey
Abstract: This paper presents the possibility of using coherent microwave scattering (CMS) for temporally resolved measurements of the electron momentum-transfer collision frequency in small plasma objects. Specifically, the electron collision frequency is inferred via phase information from microwave scattering off microplasmas operating in the mixed collisional-Thomson scattering regime. We further suggest the combination of phase and amplitude measurements to derive total electron counts and temperatures in small plasmas. An experimental validation of this concept is performed by 10.5 GHz CMS off laser-induced, variable-pressure oxygen and air plasmas.